Parenteral medication preparation by pharmacy technicians on the ward improves medication safety. Issue 2 (12th March 2012) - van de Plas, A.; Smits, C.; Mens, W.; van Leeuwen, R.; Frankfort, E.; Neef, C.
Abstract : Background: Preparation of parenteral medications is associated with considerable risk that is medication errors and risk of microbiological contamination. In Dutch hospitals parenteral medications are commonly prepared on the ward by nursing staff. In a pilot in the Maastricht University Medical Centre, pharmacy technicians instead of nurses prepared parenteral medications on the ward. For preparation specific protocols per medication in which calculation templates and double checks were included were used and hygienic measures were increased. The effect on medications errors and risk of microbiological contamination was measured. Purpose: To determine the effect of substituting preparation of parenteral medications on the ward by nurses to pharmacy technicians on medication errors as well as on the risk of microbiological contamination. Materials and Methods The study was carried out on two wards of Maastricht University Medical Centre in 2009 and 2010 Medication errors Before and after implementation of the pilot 200 preparations of parenteral drugs were randomly observed by a disguised observer and medication errors were measured. The severity of medication errors was assessed by an independent panel. Risk of microbiological contamination Before and after implementation of the pilot 200 broth simulation preparations were prepared by nurses and pharmacy technicians respectively. Microbiological contamination based on turbidity was identified. Results: Medication errors Medication errors significantly decreased from 40% in parenteral medication preparation by nurses to 1% in preparation by pharmacy technicians (p<0, 0001). The severity of medication errors decreased and double check significantly increased from 40% to 100%. Risk of microbiological contamination Risk of microbiological contamination decreased as contaminated broth simulations significantly decreased from 8% to 0% (p<0, 0001). Conclusions: Substitution of parenteral medication preparation by pharmacy technicians on the ward instead of nurses significantly reduced medication errors and the risk of microbiological contamination.